Intertextuality of Dhawabith Fiqhiyah in Mahram Breastfeeding: A Study of Article 8 of the 1974 Marriage Law and Article 39 of KHI - Fatawi Fatawi; B. Syafuri; Ahmad Hidayat (UIN Sunan Kalijaga Yogyakarta, 2025)
Ar-radhā’ah (breastfeeding) that establishes mahram status—a kinship relationship prohibiting marriage—must meet specific conditions in Islamic law, such as the child being under two years old and breastfed at least five times by a woman capable of pregnancy. These conditions are based on the Qur’an, hadith, and scholarly opinions. However, Indonesian family law, including Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), does not explicitly specify who becomes mahram through breastfeeding or the criteria involved, creating a legal gap. This study uses a qualitative, normative-empirical approach and a literature review. Julia Kristeva’s intertextuality theory is applied to analyze how classical Islamic legal texts have influenced and been transformed within Indonesian national law. The results show that although Indonesian family law does not explicitly regulate breastfeeding as a basis for mahram status, there are traces of intertextuality indicating that Islamic legal principles have been absorbed into the national legal framework, both consciously and unconsciously. Mahram relationships from breastfeeding affect marriage prohibitions and certain social interactions, but do not impact other legal aspects such as inheritance or testimony. The study recommends updating legal interpretations to fill this gap and provide legal certainty for judicial practice regarding breastfeeding-based mahram status in Indonesia. Ar-radhā’ah (penyusuan) yang menyebabkan status mahram—yaitu hubungan kekerabatan yang mengharamkan pernikahan—harus memenuhi syarat tertentu menurut hukum Islam, seperti anak disusui di bawah usia dua tahun dan disusui minimal lima kali oleh perempuan yang dapat hamil. Ketentuan ini didasarkan pada Al-Qur’an, hadis, dan pendapat para ulama. Namun, hukum keluarga di Indonesia, seperti Undang-Undang Perkawinan No. 1 Tahun 1974 dan Kompilasi Hukum Islam (KHI), tidak secara eksplisit mengatur siapa yang menjadi mahram karena penyusuan dan syarat-syaratnya, sehingga menimbulkan kekosongan hukum. Penelitian ini menggunakan pendekatan kualitatif dengan metode normatif-empiris dan kajian kepustakaan. Teori intertekstualitas dari Julia Kristeva digunakan untuk menganalisis bagaimana teks hukum nasional menyerap dan mentransformasikan makna dari sumber hukum Islam klasik. Hasil penelitian menunjukkan bahwa meskipun hukum nasional tidak secara eksplisit mengatur penyusuan sebagai sebab mahram, terdapat jejak intertekstualitas yang menunjukkan bahwa prinsip-prinsip hukum Islam telah terserap dalam sistem hukum Indonesia. Hubungan mahram akibat penyusuan berdampak pada larangan pernikahan dan interaksi sosial, namun tidak memengaruhi aspek hukum lain seperti waris atau kesaksian. Diperlukan pembaruan tafsir hukum untuk mengisi kekosongan ini dan memberikan kepastian hukum dalam praktik peradilan.